Petrographical study of the Sarmatian interval on Caragele structure based on drill cuttings (Buzau County, Romania) - Mihai Ciocirdel; Dan Romulus Jacota (Energy Exploration & Exploitation)
The Moesian platform has been extensively studied both from the tectonic point of view and from the perspective of its sedimentary bed which is rich in hydrocarbon resources. Extensive research has shown that the Moesian platform consists of Paleozoic sedimentary formations having their accouchement in four cycles, which according to in the Ordovician, Silurian, lower Devonian (dark and leaden argillites), upper Devonian (bituminous dolomites with pyritization) and mid-Triassic (muschelkalk) period, the oil and gas genesis took place. Moreover, such resources have been traced in rocks of all ages, including in the ones from the fourth sedimentation cycle. The present paper offers insight into the lithology and petrographical features of the Sarmatian stage since there is a lack of detailed petrographic published data regarding this topic. The study highlights the lithology, offering detailed petrographical features for the Sarmatian on a petroliferous structure located in the eastern part of the platform. Fossil and palynological correlations have been employed by numerous authors, resulting in a lack of focus on lithological correspondence, which is mainly due to the absence of scarce presence of available data on the Sarmatian. We therefore hold firm belief that our study could help develop future links and serve as a knowledge database.